Public-sex: viewer discourse on Deerborn's 'homemade' gay porn. Issue 1 (3rd April 2017) - Brennan, Joseph
ABSTRACT: This paper reads viewer discourse on a popular series of gay public-sex videos shared online, known as 'Deerborn'. Deerborn presented itself as occupying a place 'in-between' commercial and amateur pornography: both free of the 'fantasy constraints' of commercial pornography, yet also mobilising an audience following that allowed it to compete with more commercial offerings. Discourse on these videos offers insight into audience interest in and personal experiences of public-sex. Nominated are three key themes: space, participation and anxiety. The space theme is used as a structuring device in the second half of this paper, allowing for consideration of the settings in which the scenes take place. Yet, the focus of this paper remains on the commentary of viewers. Evidenced through this discourse is a continued interest among gay men in public-sex, with these videos serving as both vicarious viewing, and as catalyst for participants to share their own experiences of public-sex.